1962
DOI: 10.1002/macp.1962.020550106
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the alkali catalysed condensation of o‐ and p‐methylol phenols by themselves and with phenol

Abstract: The kinetics of the alkali-catalysed condensation of ortho and para nlethylol phenols, each by itself and with phenol has been studied under various experimental conditions with the help of quantitative paper chromatography. At low concentrations of the reactants and catalyst, the self-condensation of saligenin gives mainly 3-methyl01 2',4-dihydroxy diphenyl methane (DPM) and that of p-methylol phenol 5-methyl01 2,4'-DPM, the apparent first-order rate constant a t 80°C. and activation energy being 1.60.10-5 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…b, in which the carbocation is a powerful electrophile. The reaction is considered to occur between a neutral monomer and an anionic monomer . One possible mechanism involves the attack of the electron‐rich, hydroxymethyl substituted ring carbon by a QM carbocation with subsequent emission of a formaldehyde molecule as illustrated in Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…b, in which the carbocation is a powerful electrophile. The reaction is considered to occur between a neutral monomer and an anionic monomer . One possible mechanism involves the attack of the electron‐rich, hydroxymethyl substituted ring carbon by a QM carbocation with subsequent emission of a formaldehyde molecule as illustrated in Fig.…”
Section: Discussionsupporting
confidence: 83%
“…For the phenolate salts of 2‐HMP and 4‐HMP, the 13 C chemical shifts for the substituted ring carbons are found in the range of 129.62 to 130.12 ppm for 2‐HMP and 126.85 to 128.68 ppm for 4‐HMP. The higher electron density of the 4‐HMP ring carbon is in accord with the established self‐condensation reactivity order of 4‐4′ > 4‐2′ > 2‐2′ …”
Section: Discussionsupporting
confidence: 83%
“…The S N 2 mechanism shown in Figure 2 as reaction (2) was also suggested by some early reports [9,10,11,12,13]. However, in the study of Higuchi et al on the self-condensation of 2-HMP ( o -HMP) [15], the authors concluded that the reaction is of genuine first-order and any bimolecular mechanism should be ruled out.…”
Section: Resultsmentioning
confidence: 62%
“…The kinetics and mechanisms of the individual reactions in the PF system are apparently the key issues and also the foundation for understanding the chemistry of PF. However, by surveying the literature from the middle of the last century to recent years, discrepant results for the kinetics and mechanisms of the base-catalyzed condensation reactions between hydroxymethylphenols (HMPs) have been reported [9,10,11,12,13,14,15,16,17,18,19]. In some earlier studies, the condensations of HMPs were reported to be first-order [9,10,11], pseudo-first-order or second-order [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…From eqs. (5) and (8) it has been found that kl = nk. Thus, k l was calculated with the help of the overall rate constant k .…”
Section: Calculation Of Stepwise Rate Constants P-cresol Reacts With mentioning
confidence: 98%